Melodrama as utopia in The Silence of Others. - McBride, Nathaniel (Hispanic Review)
The acclaimed documentary The Silence of Others (Carracedo and Bahar, 2018) follows the recent efforts of victims of persecution during the Spanish Civil War and subsequent dictatorship (1936–1975) to achieve justice measures. This article demonstrates that the documentary employs melodramatic conventions to establish the plaintiffs' cause as just. These conventions include utopian gardens and dystopian prisons, Christian imagery, a vow of silence, and a climactic public recognition of virtue. However, this melodramatic framework simplifies the film's historical content, avoiding nuances such as the "Law of Historical Memory" and the complicity of the Partido Socialista Obrero Español in democratic Spain's history of forgetting. Likewise, the documentary offers only a minimal discussion of exhumation funding and essentializes but does not distort the Second Spanish Republic. This film exemplifies how melodramatic narratives can illustrate a utopia, in Paul Ricœur's terms: an idealized ideology that generates counterhegemonic political knowledge.